Introducing CCD1 into isolated Rhodotorula strain enhances flavor production and improves cigar fermentation - Guo, Sida; Li, Yasen; Zhu, Beibei; Zhang, Qianying; Yang, Zhen; Jia, Yun; Zhou, Quanwei; Zhang, Zhengcheng; Li, Dongliang (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction The fermentation process plays an important role in enhancing the quality of cigar tobacco leaves. Through fermentation, microbial metabolism can degrade aromatic precursors and macromolecules, which increases the content of aroma compounds and reduces irritancy of tobacco leaves. Methods To further enhance the fermentation effect of cigar tobacco leaves, a Rhodotorula strain (Rh3), capable of producing carotenoids and improving fermentation quality, was isolated from cigar tobacco leaves. Subsequent genetic engineering techniques introduced the carotenoid cleavage dioxygenase 1 (CCD1) gene into the isolated Rh3. Results The modified Rh3 exhibits a significant increase in carotenoid degradation products compared with the original Rh3 in culture medium (from 0.29 μg/mg to 15 μg/mg). Subsequent cigar tobacco leaf fermentation experiments revealed that the modified Rh3 produced 65.9% more carotenoid degradation products compared to the control group, outperforming the original strain, which achieved a 41.4% increase. Furthermore, the modified strain preserves its ability to improve the intrinsic chemical composition of cigar tobacco leaves. Discussion We show here that modified Rh3 can increase the content of carotenoid degradation products, thereby enhancing the fermentation effect of cigar tobacco leaves. This study presents a beneficial exploration to improve the quality of cigar tobacco leaves for future use and offers a promising strategy for producing flavor compounds from discarded tobacco leaves.